Future Pathways in Implementing the Teaching Personal and Social Responsibility Model in Spain and Portugal (Rutas futuras en la Implementación del modelo de enseñanza de la responsabilidad personal y social en España y Portugal) - Fernando Santos; Rui Neves; Melissa Parker (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Throughout the last two decades, researchers in Spain and Portugal have utilised the Teaching Personal and Social Responsibility (TPSR) to generate responsibility outcomes in Physical Education (PE) and further understand TPSR application. In order to move the field forward in these contexts, projections as to future of TPSR and guidelines for researchers are needed. The purpose of this article is to provide insights for expanding our knowledge of TPSR in Spain and Portugal. Although research on TPSR has provided useful insights on the processes and outcomes associated with TPSR-based programming, research exploring life skills transfer processes is needed. Further, an understanding of the broader socio-cultural forces that exist in schools and their influence on TPSR could provide valuable insight. Finally, few investigations have included young children. Moving forward, these insights may help expand future research by fostering reflection about TPSR in Spain and Portugal.